STRATEGI PENGEMBANGAN PARIWISATA BAHARI (STUDI KASUS: PANTAI EKAS KABUPATEN LOMBOK TIMUR) - Khairul Basri; I Made Murdana; M Azizurrohman (Journal Of Responsible Tourism, 2023)
This study discusses the Marine Tourism Development Strategy of Ekas Beach, East Lombok Regency. The results of the study are described in several answers to the formulation of the problem, namely to determine the potential for marine tourism attraction of Ekas Beach, then create a SWOT analysis (Strengths, Weaknesses, Opportunities, Threats), in order to find out how the marine tourism development strategy will be carried out at Ekas Beach until in making work programs that can realize the strategy. By using the method of interviews, observations, documentation studies and literature studies and approaches using qualitative descriptive. The results of this study indicate that Ekas Beach has the potential to attract competitive marine tourism from the shoreline, towering hills around the shoreline, underwater beauty, calm sea water and lobster cultivation. Ekas Beach has now begun to be managed by the Village Government and Local Communities by taking advantage of its attractiveness. Furthermore, the analysis contained in the internal factors (strengths-weaknesses) and external (opportunities-threats) from the identification of attractions and developments that have been carried out is carried out. There are four strategies that were born, namely, Alternative Strategies for Development of Marine Tourism Products, Alternative Strategies for Development of Tourism Institutions and Human Resources, Alternative Strategies for Development of Local Community-Based Tourism. Alternative Strategies for Development of Tourism Human Resources Support and Interest. Then followed up in work programs.